Efficacy of intravitreal dexamethasone implant used as monotherapy for the treatment of macular edema in non-infectious uveitis: a retrospective analysis - Gupta, Rishi B.; Ilin, Julius; Gottlieb, Chloe C. (Université d'Ottawa | University of Ottawa, 2023)
Abstract Background Uveitic macular edema is a complication of acute or chronic uveitis. Current treatment regiments frequently have numerous side effects, often requiring supplemental treatment. This study investigates the efficacy of dexamethasone (DEX) intravitreal implants as monotherapy for treatment of macular edema in non-infectious intermediate, posterior or panuveitis. Methods and results Retrospective chart review of thirty patients with intermediate, posterior and panuveitis treated with DEX. Outcomes measured were central retinal thickness (CRT) and best corrected visual acuity (BCVA). Baseline measurements of CRT and BCVA were measured within 1 month prior to intravitreal DEX implant and follow up measurements were collected until 1 year post implant. 48 implants on 39 eyes of 30 patients were included in this study; 64.1% of patients had an improvement in BCVA and 65.4% had a reduction in CRT. BCVA improved from 0.285 logMAR (SD: 0.312) at baseline to 0.175 logMAR (SD: 0.194) at 1 month and was sustained thereafter. Preliminary CRT data showed a decrease from 392 $$\mu m$$ μ m (SD: $$161\mu m$$ 161 μ m ) at baseline to 303 $$\mu m$$ μ m (SD: $$80\mu m)$$ 80 μ m ) at 1 month and 313 $$\mu m$$ μ m (SD: $$44\mu m)$$ 44 μ m ) at 12 months. Conclusions The DEX implant as monotherapy for macular edema in non-infectious uveitis was associated with a reduction in CRT and improvement in BCVA. The DEX implant, used as a monotherapy in eyes with intermediate, posterior and panuveitis, has the potential to treat uveitis without oral corticosteroid or other immunomodulatory therapy.